Electric-field stabilized vortex nematicons in low-birefringent nematic liquid crystals - Kwaśny, Michał; Karpierz, Mirosław; Laudyn, Urszula (Photonics Letters of Poland, 2025)
We report on the generation and electric-field stabilization of scalar vortex nematicons in a low-birefringence nematic liquid crystal (LB NLCs). Using mixture 903, we demonstrate self-confined vortex beams that preserve their topological charge and maintain a doughnut-shaped profile over millimetre-scale distances. Utilizing a low-frequency electric field, we show that temporal fluctuations, polarization mixing, and azimuthal distortions are substantially reduced. Interferometric measurements confirm robust phase singularities, while intensity maps reveal enhanced symmetry and stability as the voltage increases. The combined effects of LB and electric-field-induced fluctuation quenching establish the 903 NLCs mixture as a promising platform for stable vortex spatial solitons and tunable structured-light photonic applications. Full Text: PDF References W.J. Firth, D.V. Skryabin, "Optical Solitons Carrying Orbital Angular Momentum", Phys. Rev. Lett. 79, 2450 (1997). CrossRef Y.V. Izdebskaya, A.S. Desyatnikov, G. Assanto, Y.S. Kivshar, "Dipole azimuthons and vortex charge flipping in nematic liquid crystals", Opt. Express 19, 21457-21466 (2011). CrossRef Y.V. Izdebskaya, V.G. Shvedov, P.S. Jung, W. Krolikowski, "Stable vortex soliton in nonlocal media with orientational nonlinearity", Opt. Lett. 43(1), 66-69 (2018). CrossRef Z. Xu, N. F. Smyth, A. A. Minzoni, Y. S. Kivshar, "Vector vortex solitons in nematic liquid crystals", Opt. Lett. 34(9), 1414-1416 (2009). CrossRef G. Assanto, M. A. Karpierz, "Nematicons: self-localised beams in nematic liquid crystals", Liq. Cryst. 36(10), 1161-1172 (2009). CrossRef M. Peccianti, G. Assanto, "Nematicons", Phys. Rep. 516, 147-208 (2012). CrossRef G. Assanto, "Nematicons: reorientational solitons from optics to photonics", Liq. Cryst. Rev. 6(2), 170-194 (2018). CrossRef G. Vitrant, R. Reinisch, J.Cl. Paumier, G. Assanto, G.I. Stegeman, "Nonlinear prism coupling with nonlocality", Opt. Lett. 14(16), 898-890 (1989). CrossRef C. Rotschild, O. Cohen, O. Manela, M. Segev, T. Carmon, "Solitons in Nonlinear Media with an Infinite Range of Nonlocality: First Observation of Coherent Elliptic Solitons and of Vortex-Ring Solitons", Phys. Rev. Lett. 95(21), 213904 (2005). CrossRef S. Skupin, O. Bang, D. Edmundson, W. Krolikowski, "Stability of two-dimensional spatial solitons in nonlocal nonlinear media", Phys. Rev. E 73(6), 066603 (2006). CrossRef N. Smyth, A. Piccardi, A. Alberucci, G. Assanto, "Highly nonlocal optical response: Benefit or drawback?", J. Nonl. Opt. Phys. Mat. 25(4), 1650043 (2017). CrossRef M. Kwasny, D. Hertsch, U. Laudyn, "Experimental analysis of Airy beam self-localization in nematic liquid crystals", Opt. Lett., 49 (20), 5905-5908 (2024) CrossRef U. Laudyn, M. Kwasny, M. Karpierz, G. Assanto, "Vortex nematicons in planar cells", Opt. Express 28, 8282-8290 (2020) CrossRef M. Kwasny, M. Karpierz, G. Assanto, U. Laudyn, "Optothermal vortex-solitons in liquid crystals", Opt. Letters 45, 2451-2453 (2020) CrossRef A. A. Minzoni, N. F. Smyth, Z. Xu, and Y. S. Kivshar, "Stabilization of vortex-soliton beams in nematic liquid crystals", Phys. Rev. A 79, 063808 (2009). CrossRef G. Assanto, A. A. Minzoni, and N. F. Smyth, "Vortex confinement and bending with nonlocal solitons", Opt. Lett. 39(3), 509-512 (2014) CrossRef P. S Jung, Y. Izdebskaya, V. G Shvedov, D. N Christodoulides, W. Krolikowski, "Formation and stability of vortex solitons in nematic liquid crystals", Opt. Lett. 46(1), 62-65 (2025) CrossRef N. Karimi, A. Alberucci, M. Virkki, A. Priimägi, M. Kauranen, and G. Assanto, "Quenching nematicon fluctuations via photo-stabilization", Photon. Lett. Pol. 8 (1), 2-4 (2016) CrossRef J. F. Henninot, J. F. Blach, M. Warenghem, "The investigation of an electrically stabilized optical spatial soliton induced in a nematic liquid crystal", J. Opt. A:Pure Appl. Opt. 10, 085104 (2008) CrossRef U. Laudyn, M. Kwasny, M. Karpierz, and G. Assanto, "Electro-optic quenching of nematicon fluctuations ", Opt. Lett. 44(1), 167-170 (2019). CrossRef M. Kwasny, U. A. Laudyn, F. A. Sala, A. Alberucci, M. A. Karpierz, and G. Assanto, "Self-guided beams in low-birefringence nematic liquid crystals", Phys. Rev. A 86(1), 01382 (2012). CrossRef B. Klus, U. A. Laudyn, M. A. Karpierz, and B. Sahraoui, "All-optical measurement of elastic constants in nematic liquid crystals", Opt. Express 22(24), 30257-30266 (2014). CrossRef I. C. Khoo, "Nonlinear optics of liquid crystalline materials", Phys. Rep. 471, 221 (2009) CrossRef